Drug–drug interaction of microdose and regular-dose omeprazole with a CYP2C19 inhibitor and inducer - Park G; Bae SH; Park W; Han S; Park M; Shin S; Shin YG; Yim DS (Dove Medical Press, 2017)
Gab-jin Park,1 Soo Hyeon Bae,1 Wan-Su Park,1 Seunghoon Han,1 Min-Ho Park,2 Seok-Ho Shin,2 Young G Shin,2 Dong-Seok Yim1,2 1Department of Clinical Pharmacology and Therapeutics, Seoul St Mary’s Hospital, PIPET (Pharmacometrics Institute for Practical Education and Training), College of Medicine, Catholic University of Korea, Seoul, South Korea; 2College of Pharmacy, Chungnam National University, Daejeon, South Korea Purpose: A microdose drug–drug interaction (DDI) study may be a valuable tool for anticipating drug interaction at therapeutic doses. This study aimed to compare the magnitude of DDIs at microdoses and regular doses to explore the applicability of a microdose DDI study. Patients and methods: Six healthy male volunteer subjects were enrolled into each DDI study of omeprazole (victim) and known perpetrators: fluconazole (inhibitor) and rifampin (inducer). For both studies, the microdose (100 µg, cold compound) and the regular dose (20 mg) of omeprazole were given at days 0 and 1, respectively. On days 2–9, the inhibitor or inducer was given daily, and the microdose and regular dose of omeprazole were repeated at days 8 and 9, respectively. Full omeprazole pharmacokinetic samplings were performed at days 0, 1, 8, and 9 of both studies for noncompartmental analysis. Results: The magnitude of the DDI, the geometric mean ratios (with perpetrator/omeprazole only) of maximum concentration (Cmax) and area under the curve to the last measurement (AUCt) of the microdose and the regular dose were compared. The geometric mean ratios in the inhibition study were: 2.17 (micro) and 2.68 (regular) for Cmax, and 4.07 (micro), 4.33 (regular) for AUCt. For the induction study, they were 0.26 (micro) and 0.21 (regular) for Cmax, and 0.16 (micro) and 0.15 (regular) for AUCt. There were no significant statistical differences in the magnitudes of DDIs between microdose and regular-dose conditions, regardless of induction or inhibition. Conclusion: Our results may be used as partial evidence that microdose DDI studies may replace regular-dose studies, or at least be used for DDI-screening purposes. Keywords: drug–drug interaction, microdose, CYP2C19